A New Oidiodendron maius Strain Isolated from Rhododendron fortunei and its Effects on Nitrogen Uptake and Plant Growth - Wei, Xiangying; Chen, Jianjun; Zhang, Chunying; Pan, Dongming (Frontiers in Microbiology, 2016)
A new mycorrhizal fungal strain was isolated from hair roots of Rhododendron fortunei Lindl. grown in Huading Forest Park, Zhejiang Province, China. Morphological characterization and internal transcribed spacer (ITS) rDNA analysis suggested that it belongs to Oidiodendron maius Barron, and we designated it as strain Om19. Methods for culturing Om19 were established, and the ability of Om19 to form mycorrhizae on R. fortunei was evaluated in a peat-based substrate. Microscopic observations showed hyaline hyphae on the surface of hair roots and crowded hyphal complexes (hyphal coils) inside root cortical cells of R. fortunei after inoculation, indicating that the roots were well colonized by Om19. In a second experiment, fresh and dry weight of R. fortunei two months after Om19 inoculation were greater than uninoculated plants, and the total nitrogen (N) absorbed by plants inoculated with Om19 was greater than the uninoculated controls. qRT-PCR analysis of five genes related to N uptake and metabolism (two nitrate transporters, an ammonium transporter, glutamine synthetase, and glutamate synthase) showed that these genes were highly upregulated with 2 to 9 fold greater expression in plants inoculated with Om19 compared to uninoculated plants. In the third experiment, Om19 was inoculated into the peat-based substrate for growing Formosa azalea (R. indica ‘Formosa’). ‘Formosa’ azalea plants grown in the inoculated substrate had larger canopies and root systems compared to uninoculated plants. Our results show that Om19 could be an important microbial tool for improving production of Rhododendron plants.